Pengembangan Bahan Ajar Menulis Puisi Rakyat Berbantuan Media Gambar “Canva” Untuk Siswa Kelas Vii - Suci Cyntia Sablina Beuty Sakti Situmorang; Khairil Ansari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aims to develop teaching materials for writing Pantun (a traditional Malay poetry form) using "Canva" assisted image media in the Indonesian language subject. It seeks to analyze the feasibility of developing teaching materials for writing Pantun using "Canva" assisted image media as instructional material for the Indonesian language subject in seventh-grade Junior High School. The development method employed is the research and development method by Borg and Gall, modified by Sugiyono, involving five stages. The developmental stages encompass potential and problem analysis, data collection, developmental product design, validation, and product design revision. The development was validated by two validators: a subject matter expert with a rating reaching 84% falling into the highly feasible category, media expert validation with a rating reaching 81% categorized as highly feasible, and teacher validation with a rating of 90%. Based on the overall feasibility assessments of the presented teaching materials, the development of Teaching Materials for Writing Pantun Using "Canva" Assisted Image Media for seventh-grade holds a highly feasible quality and can be accepted as one of the instructional materials.